2020
DOI: 10.1021/acs.jpcc.0c02715
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Induced Optical Anisotropy in Monolayer MoS2

Abstract: In-plane optical anisotropy has been detected from monolayer MoS 2 grown on a-plane (112̅ 0) sapphire substrate in the ultraviolet−visible wavelength range. Based on the measured optical anisotropy, the energy differences between the optical transitions polarized along the ordinary and extraordinary directions of the underlying sapphire substrate have been determined. The results corroborate comprehensively with the dielectric environment induced modification on the electronic band structure and exciton bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…As for the center of bubble, the bandgap transition peak is split into two opposite derivative peaks, and the reflectance difference intensity is greatly increased, indicating strong anisotropic optical transition under strain. 52 Furthermore, except for the interferenceinduced negative ΔR/R peak (∼1.83 eV), two obvious periodical peaks located at ∼1.92 and ∼2.39 eV appear at the center of bubble, which is the strong evidence of optical interference in the bubble, indicating that optical interference plays an important role in the modulation of in-plane optical anisotropy of ReS 2 /gr heterobubbles. In short, with an induced bubble under ReS 2 , the optical anisotropy can be modulated by both strain and optical interference.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…As for the center of bubble, the bandgap transition peak is split into two opposite derivative peaks, and the reflectance difference intensity is greatly increased, indicating strong anisotropic optical transition under strain. 52 Furthermore, except for the interferenceinduced negative ΔR/R peak (∼1.83 eV), two obvious periodical peaks located at ∼1.92 and ∼2.39 eV appear at the center of bubble, which is the strong evidence of optical interference in the bubble, indicating that optical interference plays an important role in the modulation of in-plane optical anisotropy of ReS 2 /gr heterobubbles. In short, with an induced bubble under ReS 2 , the optical anisotropy can be modulated by both strain and optical interference.…”
Section: Resultsmentioning
confidence: 87%
“…As shown in Figure e, the peak located at 1.47 eV is assigned to the direct transition from valence band (VB) to conduction band (CB), which corresponds to the bandgap of few-layer ReS 2 , while the strong negative peak at 1.83 eV belongs to the Fabry–Perot interference at the Si/SiO 2 /graphene/ReS 2 interface because ReS 2 has no transition at a photon energy of ∼1.83 eV (Note S12). As for the center of bubble, the bandgap transition peak is split into two opposite derivative peaks, and the reflectance difference intensity is greatly increased, indicating strong anisotropic optical transition under strain . Furthermore, except for the interference-induced negative Δ R / R peak (∼1.83 eV), two obvious periodical peaks located at ∼1.92 and ∼2.39 eV appear at the center of bubble, which is the strong evidence of optical interference in the bubble, indicating that optical interference plays an important role in the modulation of in-plane optical anisotropy of ReS 2 /gr heterobubbles.…”
Section: Results and Discussionmentioning
confidence: 91%
“…Optical anisotropy in MoS 2 nanosheets can be significant, as was recently indicated in a report by Volkov and co-workers on the giant optical anisotropy in MoS 2 nanosheets, showcasing a large birefringence of Δ n = 3 and Δ n = 1.5 for visible and infrared (IR) light, respectively . In addition, anisotropic optical effects in MoS 2 may be substrate-induced due to morphological effects or crystallographically dictated symmetry breaking and defectivity. , Excitonic emission by MoS 2 nanosheets is of particular interest for optoelectronic devices. MoS 2 photoluminescence (PL) can be manipulated through defect engineering and plasmonic coupling.…”
mentioning
confidence: 87%
“…6 In addition, anisotropic optical effects in MoS 2 may be substrate-induced due to morphological effects 22−24 or crystallographically dictated symmetry breaking and defectivity. 27,28 Excitonic emission by MoS 2 nanosheets is of particular interest for optoelectronic devices. MoS 2 photoluminescence (PL) can be manipulated through defect engineering and plasmonic coupling.…”
mentioning
confidence: 99%
“…[140] Recently, it has been reported that the dielectric environment can induce the modification of electronic band structure and exciton binding in monolayer MoS 2 . [141] Therefore, monolayer MoS 2 could exhibit optical anisotropy.…”
Section: Symmetry Breaking Of Traditional Isotropic 2d Materialsmentioning
confidence: 99%